2019
DOI: 10.1016/j.celrep.2019.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Activities of Two Neuronal Splicing Factors Switch the GABA Effect from Excitatory to Inhibitory by Regulating REST

Abstract: SUMMARY A truncating mutation in the mouse Srrm4 gene, which encodes a neuronal splicing factor, causes alternative splicing defects selectively in the ear. The mechanism by which splicing is preserved in the brain of these mice is not known. Here, we show that SRRM3 limits the Srrm4 mutation-associated defects to the ear and that, in cortical neurons, overlapping SRRM3-SRRM4 activity regulates the development of interneuronal inhibition. In vitro, SRRM3 and SRRM4 regulate the same splicing events, but a mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 42 publications
4
43
0
Order By: Relevance
“…Temporal and anatomic differences in alternative splicing are implicated in developmental changes in molecular function 70 . Our single-cell isoform data enable, for the first time, the illumination of alternative splicing regulation across cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal and anatomic differences in alternative splicing are implicated in developmental changes in molecular function 70 . Our single-cell isoform data enable, for the first time, the illumination of alternative splicing regulation across cell types.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that in cortical neurons SRRM4 and SRRM3 act redundantly in regulating the alternative splicing of Rest (Nakano et al, 2019). However, in the utricle, SRRM4 is critical for the alternative splicing of Rest (Fig 2B), likely because utricular expression of Srrm3 is minimal in the absence of SRRM4 (Fig 2A).…”
Section: Ohcs Differ From Ihcs and Vhcs With Respect To Srrm4-indepenmentioning
confidence: 93%
“…We tested whether Srrm3 expression is necessary for the Tg(DnRest)-dependent survival of IHCs and VHCs in Srrm4 bv/bv mice. To reduce Srrm3 expression in Tg(DnRest);Srrm4 bv/bv mice, we took advantage of a recently produced gene trap allele of Srrm3 (Srrm3 gt ) (Nakano et al, 2019). Tg(DnRest);Srrm3 gt/gt ;Srrm4 bv/bv mice were generated and used for qRT-PCR and histological analyses.…”
Section: Tg(dnrest) Rescues Ihcs and Vhcs But Fails To Restore Splicimentioning
confidence: 99%
See 2 more Smart Citations